Involvement of intrinsic mitochondrial pathway in neosergeolide-induced apoptosis of human HL-60 leukemia cells: The role of mitochondrial permeability transition pore and DNA damage - Coelho Cavalcanti, Bruno (Pharmaceutical Biology, 2020)
Context: Quassinoids are biologically active secondary metabolites found exclusively in the Simaroubaceae family of plants. These compounds generally present important biological properties, including cytotoxic and antitumor properties. Objective: In the present study, the cytotoxic effects of neosergeolide, a quassinoid isolated from Picrolemma sprucei Hook. f., were evaluated in human promyelocytic leukemia cells (HL-60). Materials and methods: Cytotoxicity and antiproliferative effects were evaluated by the MTT assay, May-Grünwald-Giemsa's staining, BrdU incorporation test, and flow cytometry procedures. The comet assay and micronuclei analysis were applied to determine the genotoxic and mutagenic potential of neosergeolide. Results: After 24h exposure, neosergeolide strongly inhibited cancer cell proliferation (IC 50 0.1 μM), and its activity seemed to be selective to tumor cells because it had no antiproliferative effect on human peripheral blood mononuclear cells (PBMC) at tested concentrations. Apoptosis was induced at submicromolar concentrations (0.05, 0.1, and 0.2 μM) as evidenced by morphological changes, mitochondrial depolarization, phosphatidylserine externalization, caspases activation, and internucleosomal DNA fragmentation. Additionally, neosergeolide effects were prevented by cyclosporine A (CsA), an inhibitor of the mitochondrial permeability transition (MPT) pore, which reinforced the participation of intrinsic pathways in the apoptotic process induced by this natural quassinoid. Direct DNA damage was further confirmed by comet assay and cytokinesis-block micronucleus test. Discussion and conclusion: The present study provided experimental evidence to support the underlying mechanism of action involved in the neosergeolide-mediated apoptosis. In addition, no antiproliferative effect or DNA damage effect of neosergeolide was evident in PBMC, highlighting its therapeutic potential. © 2012 Informa Healthcare USA, Inc.